GREENHOUSE MONITORING SYSTEM USING INTERNET OF THINGS. - V., Kaviyarasi; R., Maheshwari (Proteus, 2022)
Keeping plants healthy and prosperous requires the best possible growing environment. But staying on top of all environmental changes and equipment statuses or failures can be a challenge. Green house temperature should not go below a certain degree, High humidity can result to crop transpiration, condensation of water vapor on various greenhouse surfaces, and water evaporation from the humid soil. Maintaining a controlled temperature within a greenhouse environment is crucial. Temperature fluctuations can damage or kill your plants in only a few hours. Internet of Things(IOT) is one of the latest advances in Information and Communication Technologies, providing global connectivity and management of sensors, devices, users with information. In today's greenhouses, many parameter measurements are required to monitor and control for the good quality and productivity of plants. The sensors used here are moisture sensor, Temperature & Humidity sensor. The other important part of this project is that it is fully automatic. Arduino automatically turns on and turns off the appliances. From the data's received, Raspberry PI3 automatically controls Moisture and Temperature. Where the recorded temperature and humidity are stored in a cloud database and the results are displayed in a webpage, from where the user can view them directly.